(untitled) (Journal of Mathematical Study, 2024)
Conformation changes control the function of many proteins and thus much of biology. But it is not always clear what conformation means: is it the distribution of mass? Is it the distribution of permanent charge, like that on acid and base side chains? Is it the distribution of dielectric polarization? Here we point out that one of the most important conformation changes in biology can be directly measured and the meaning of conformation is explored in simulations and theory. The conformation change that underlies the main signal of the nervous system produces a displacement current—NOT an ionic current—that has been measured. Macroscopic measurements of atomic scale currents are possible because total current (including displacement current) is everywhere exactly the same in a one dimensional series system like a voltage clamped nerve membrane, as implied by the mathematical properties of the Maxwell Ampere law and the Kirchhoff law it implies. We use multiscale models to show how the change of a single side chain is enough to modulate dielectric polarization and change the speed of opening of voltage dependent channels. The idea of conformation change is thus made concrete by experimental measurements, theory, and simulations.